Using the organizational network analysis to build competitiveness on the example of enterprise energy sector - Wawrzynek Łukasz (Management, 2016)
Contemporary organizations operate in dynamic, complex markets. One of the directions of their development is the increase of competitiveness level. This level must be based on factors for building competitive advantage, clear for the given organization, or, in a broader sense, based on general conditions for the increase of competitiveness. One of these directions could be innovation, which would lead to development and the gaining of new markets. Being innovative depends on the ideas and their implementation. This in turn depends on knowledge, primarily tacit knowledge, which is associated with the employees. To identify it, and next lead to its diffusion and application, the organization must learn the dependencies in which employees function, and match to them certain actions that would result in the increase of innovation potential. The learning of the actual relations is possible with the application of the organizational network analysis. This paper presents an example of applying organizational networks in an enterprise, on the basis of a conducted study. The results suggest that such tools are useful and that the organization, after the interventions it launched, achieves in the analyzed area a level of competitiveness higher than in other areas.